2018
DOI: 10.3390/molecules23030687
|View full text |Cite
|
Sign up to set email alerts
|

Miro1 Enhances Mitochondria Transfer from Multipotent Mesenchymal Stem Cells (MMSC) to Neural Cells and Improves the Efficacy of Cell Recovery

Abstract: A recently discovered key role of reactive oxygen species (ROS) in mitochondrial traffic has opened a wide alley for studying the interactions between cells, including stem cells. Since its discovery in 2006, intercellular mitochondria transport has been intensively studied in different cellular models as a basis for cell therapy, since the potential of replacing malfunctioning organelles appears to be very promising. In this study, we explored the transfer of mitochondria from multipotent mesenchymal stem cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
146
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(152 citation statements)
references
References 60 publications
3
146
0
3
Order By: Relevance
“…Accumulating evidence has suggested that mitochondrial transfer from MSCs is a novel strategy for the regeneration of various damaged cells via rescue of their respiratory activities. Accumulating evidence has shown that mitochondrial transfer occurs via TNTs, gap junctions, microvesicles, cell fusion and transfer of isolated mitochondria [132,[242][243][244][245]. So far, mitochondrial transfer from MSCs has demonstrated protective effects in lung injury, bronchial epithelial injury, allergic diseases, damaged cardiomyocytes, alkali-burnt corneal epithelial cells, kidney injury, ischemic damage, neurotoxicity, and spinal cord injury [132,[246][247][248][249][250][251][252][253].…”
Section: Mitochondrial Transfermentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating evidence has suggested that mitochondrial transfer from MSCs is a novel strategy for the regeneration of various damaged cells via rescue of their respiratory activities. Accumulating evidence has shown that mitochondrial transfer occurs via TNTs, gap junctions, microvesicles, cell fusion and transfer of isolated mitochondria [132,[242][243][244][245]. So far, mitochondrial transfer from MSCs has demonstrated protective effects in lung injury, bronchial epithelial injury, allergic diseases, damaged cardiomyocytes, alkali-burnt corneal epithelial cells, kidney injury, ischemic damage, neurotoxicity, and spinal cord injury [132,[246][247][248][249][250][251][252][253].…”
Section: Mitochondrial Transfermentioning
confidence: 99%
“…Miro1 binds the mitochondria to KIF5 motor protein together with other accessory proteins like Miro2, TRAK1, TRAK2, Myo10, and Myo19, thus forming a motor-adaptor complex that coordinates the mitochondrial movement at intercellular and intracellular levels [241,242]. Knock-down of Miro1 in MSCs inhibits mitochondrial donation, thus reducing their therapeutic effects in bronchial epithelial injury [254]; in contrast, Miro1overexpression in MSCs leads to enhanced beneficial effects [242,255,256]. Apart from Miro1, Zhang et al found that TNF-α induces TNT formation in MSCs via the TNF-α/NF-κB/TNFαIP2 signalling pathway, which facilitates mitochondrial transfer to cardiomyocytes.…”
Section: Mitochondrial Transfermentioning
confidence: 99%
“…MSC‐derived extracellular matrix further contributes to the beneficial effects of MSCs on islet function, and a number of studies have highlighted the importance of direct MSC‐islet cell‐cell contact for islet functional survival . Studies in other tissues have also demonstrated the capacity of MSCs to act as mitochondria donors by transferring functional mitochondria directly to adjacent cocultured cells in inflammatory and ischemic disease settings, resulting in the rescue of aerobic respiration . Insulin secretion from β‐cells is primarily controlled by mitochondrial ATP generation in response to elevations in extracellular glucose, and islet oxygen consumption rate (OCR) is a key predictor of islet transplantation outcome .…”
Section: Introductionmentioning
confidence: 99%
“…Mitochondrial transfer from one cell type to another is not exclusive to astrocytes and neurons. For example, we and others have shown that mesenchymal stem cells transfer mitochondria to damaged neuronal stem cells thereby improving stem cell survival and mitochondrial membrane potential in the recipient cells (Boukelmoune et al, 2018;Gheusi and Lledo, 2014; M. L. Babenko et al, 2018). Transfer of mitochondria from one cell to another occurs via multiple mechanisms such as release and uptake of vesicles, transfer via gap junctions, and transfer via F-actin based tunneling nanotubes (Rogers and Bhattacharya, 2013;.…”
Section: Introductionmentioning
confidence: 99%